2019
DOI: 10.37901/jcphp18-00028
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Pharmacist-Led Patient Home Visits

Abstract: Introduction Patients with chronic diseases such as hypertension and diabetes often experience difficulties managing complex medication regimens. A promising method for identifying and addressing medication-related problems is pharmacist provision of patient home visits. Pharmacist home visits could alleviate the burden on both patients and providers for the purposes of maintenance medication and goal-achievement assessment. Methods A pharmacist home visit program was developed utilizing social workers to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This work was possible through a grant-funded project designed to increase rural patient access to quality healthcare. 10 Because this work was funded, the project focus was on demonstrating the benefit of the pharmacist as part of a home visit healthcare team rather than on cost savings or financial benefits. Identifying ways to bill for these services to make this work sustainable beyond the funded project is an ongoing effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work was possible through a grant-funded project designed to increase rural patient access to quality healthcare. 10 Because this work was funded, the project focus was on demonstrating the benefit of the pharmacist as part of a home visit healthcare team rather than on cost savings or financial benefits. Identifying ways to bill for these services to make this work sustainable beyond the funded project is an ongoing effort.…”
Section: Discussionmentioning
confidence: 99%
“…In Washington State ongoing work is being conducted to implement comprehensive medication review (CMR) services in rural and underserved communities. 10 As part of a grant-funded project, rural patient CMRs were conducted by a community pharmacist at an outpatient clinic beginning Fall 2019. The project was designed for clinic physicians and nursing staff to identify and enroll up to 50 patients to be referred to a pharmacist for a CMR.…”
Section: Introductionmentioning
confidence: 99%
“…In a rural, Washington state community, a novel integrated care team including a home health nurse, a hospital pharmacist, and clinic-based physicians developed an interprofessional practice to identify and intervene with high-risk patients cared for in their clinic [ 10 ]. Clinic patients who would benefit from an in-depth medication review by the pharmacist were identified by nurses and physicians.…”
Section: Methodsmentioning
confidence: 99%
“…At the time of the visit, she was retired, but she had previously been employed as a nurse and, most recently, she was the primary caregiver for her sister until her passing. She was identified by her primary care provider and home health nurse to be a candidate for pharmacist-provided comprehensive medication review (CMR) services [ 10 ]. The patient’s past medical history included diagnoses of angina, asthma, anxiety disorder, chronic neuropathic pain, constipation, depression, diabetes, gastroesophageal reflux disease (GERD), hypertension, insomnia, migraine headaches, muscle spasms, and restless leg syndrome.…”
Section: Methodsmentioning
confidence: 99%